Towards the Thousandth CubeSat: A Statistical Overview - Thyrso Villela; Cesar A. Costa; Alessandra M. Brandão; Fernando T. Bueno; Rodrigo Leonardi (International Journal of Aerospace Engineering)
CubeSats have become an interesting innovation in the space sector. Such platforms are being used for several space applications, such as education, Earth remote sensing, science, and defense. As of May 31st, 2018, 855 CubeSats had been launched. Remote sensing application is the main sector in which CubeSats are being used, corresponding to about 45% of all applications. This fact indicates the commercial potential of such a platform. Fifty eight countries have already been involved with developing CubeSats. The most used CubeSat configuration is 3U (about 64%), followed by 1U (18%), while 6U platforms account for about 4%. In this paper, we present an analysis of the current situation regarding CubeSats worldwide, through the use of a dataset built to encompass information about these satellites. The overall success rate of the CubeSat missions is increasing over time. Moreover, considering CubeSat missions as a Bernoulli experiment, and excluding launch failures, the current success rate was estimated, as a parameter of a binomial distribution, to be about 75%. By using a logistic model and considering that the launchings keep following the current tendency, one can expect that one thousand CubeSats will be launched in 2021, within 95% certainty.